Pengaruh Kepribadian dan Budaya Organisasi Terhadap Organizational Citizenship Behavior - Rifany Kurniawan; Habibullah Jimad (Jurnal Manajemen, Ekonomi, Hukum, Kewirausahaan, Kesehatan, Pendidikan dan Informatika, 2023)
PT. Bintang Motor Group Area Lampung is part of PT. Bintang Motor Group to manage several branches in the Lampung area engaged in sales, maintenance and spare parts of official Honda motorcycles. Currently, the competition in the motorcycle industry is getting tighter, it can be seen from not achieving the target in several months in 2022. In addition, the problem of employee personality that is less professional and communication that is hampered and does not comply with some company values or culture that results in consumer dissatisfaction is a problem that must also be faced by the company. The output of solving this problem can make employees become professional and loyal individuals and obedient to the company. in fact, providing an extra role or Organizational Citizenship Behavior (OCB) behavior to achieve company targets. This study aims to determine the influence of personality and organizational culture on the OCB of PT employees. Bintang Motor Group Lampung Area. Causal research methods and the study population amounted to 175 people and a sample of 122 people. The results of the study partially showed that personality variables and organizational culture had a positive and significant effect on the OCB of PT employees. Bintang Motor Group Lampung Area.